Quantifying the efficacy of an automated facial coding software using videos of parents - Burgess, R.; Culpin, I.; Costantini, I.; Bould, H.; Nabney, I.; Pearson, R. M. (Frontiers in Psychology, 2023)
This work explores the use of an automated facial coding (AFC) software “FaceReader” (Noldus, 2014) as an alternative and/or complementary method to manual coding. We used videos of parents (fathers, n = 36; mothers, n = 29) taken from the Avon Longitudinal Study of Parents and Children (ALSPAC). The videos – obtained during real-life parent-infant interactions in the home – were coded both manually (using an existing coding scheme) and by FaceReader. We established a correspondence between the manual and automated coding categories – namely Positive, Neutral, Negative, and Surprise- before contingency tables were employed to examine the software's detection rate and quantify the agreement between manual and automated coding. By employing binary logistic regression, we examined the predictive potential of FaceReader outputs in determining manually classified facial expressions. An interaction term was used to investigate the impact of gender on our models, seeking to estimate its influence on the predictive accuracy. We found that the automated facial detection rate was low (25.2% for fathers, 24.6% for mothers) compared to manual coding, and discuss some potential explanations for this (e.g., poor lighting and facial occlusion). Our logistic regression analyses found that Surprise and Positive expressions had strong predictive capabilities, while Negative expressions performed poorly. Mothers' faces were more important for predicting Positive and Neutral expressions, while fathers' faces were more important in predicting Negative and Surprise expressions. We discuss the implications of our findings in the context of future automated facial coding studies, and we emphasise the need to consider gender-specific influences in automated facial coding research.